Abl kinases can function as suppressors of tumor progression and metastasis - Marchal, Melissa A.; Moose, Devon L.; Varzavand, Afshin; Jordan, Nicole E.; Taylor, Destiney; Tanas, Munir R.; Brown, James A.; Henry, Michael D.; Stipp, Christopher S. (Frontiers in Oncology, 2023)
Abl family kinases function as proto-oncogenes in various leukemias, and pro-tumor functions have been discovered for Abl kinases in many solid tumors as well. However, a growing body of evidence indicates that Abl kinases can function to suppress tumor cell proliferation and motility and tumor growth in vivo in some settings. To investigate the role of Abl kinases in tumor progression, we used RNAi to generate Abl-deficient cells in an orthotopic model of prostate cancer metastasis. Reduced Abl family kinase expression resulted in a highly aggressive, metastatic phenotype in vivo that was associated with AKT pathway activation, increased growth on 3D collagen matrix, and enhanced cell motility in vitro. Inhibiting AKT pathway signaling abolished the increased 3D growth of Abldeficient cells, while treatment with the Abl kinase inhibitor, imatinib, promoted 3D growth of multiple additional tumor cell types. Moreover, Abl kinase inhibition also promoted soft-agar colony formation by pre-malignant fibroblasts. Collectively, our data reveal that Abl family kinases can function to suppress malignant cell phenotypes in vitro, and tumor progression and metastasis in vivo.